2017
DOI: 10.1111/joss.12282
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a descriptive analysis and instrumental measurements (electronic nose and electronic tongue) for the sensory profiling of Korean fermented soybean paste (doenjang)

Abstract: The objective of this study was to investigate the feasibility of using an electronic nose (e‐nose) and electronic tongue (e‐tongue) in the sensory profiling of doenjang, a fermented soybean paste. The descriptive analysis of doenjang by trained panelists was compared with that assessed using the e‐nose and e‐tongue. Eighteen aroma/taste/flavor attributes developed by trained panels from 14 doenjang samples were compared with the results from e‐nose and e‐tongue measurements. The e‐nose detected 11 volatile co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…A stronger brown color was significantly stronger in M7, and TS8–10, which had traditional doenjang characteristics ( p < .05); this is in accordance with the results of previous studies (Jung et al, ; Kim & Lee, ; Kim et al, ). It has been reported that doenjang manufactured through a modified method typically has a lighter color than TSD, mainly because modified methods involve the inoculation of A. oryzae , which results in a lighter color (Kim et al, ).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…A stronger brown color was significantly stronger in M7, and TS8–10, which had traditional doenjang characteristics ( p < .05); this is in accordance with the results of previous studies (Jung et al, ; Kim & Lee, ; Kim et al, ). It has been reported that doenjang manufactured through a modified method typically has a lighter color than TSD, mainly because modified methods involve the inoculation of A. oryzae , which results in a lighter color (Kim et al, ).…”
Section: Resultssupporting
confidence: 92%
“…High intensities of alcohol aromatics have been noted in doenjang in two cases: (a) when alcohol is artificially added to doenjang during manufacturing to minimize the growth of undesirable microorganisms during storage and distribution, and (b) when alcohol naturally forms during doenjang fermentation, particularly in those doenjang samples with a high carbohydrate and low salt content (Chiou, Ferng, & Beuchat, ; Kim et al, ; Park, Lee, Kim, & Lee, ). The typical method of manufacturing commercial doenjang involves the addition of ethyl alcohol to increase the length of preservation; hence, many previous studies have reported a high level of alcohol aromatics in doenjang made using a modified method (Jung et al, ; Kim et al, ). In the present study, high intensities of alcohol aromatics were observed in TS8 seemed that the company added ethyl alcohol for preservation like modified method.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations